METHODOLOGY FOR TRAINING FUTURE MUSIC TEACHERS TO WORK WITH CHILDREN WITH DISABILITIES - Syomkina Adiba Mingirovna (Web of Journals Publishing, 2023)
The article discusses the problems of music education for children with disabilities.
Keywords: music education, children with disabilities, correctional methods.